Wall shear stress estimated with phase contrast MRI in an in vitro and in vivo intracranial aneurysm. Issue 4 (15th February 2013) - van, Pim; Potters, Wouter V.; Guédon, Annetje; Schneiders, Joppe J.; Marquering, Henk A.; Majoie, Charles B.; vanBavel, Ed; Nederveen, Aart J.
<x xml:space="preserve">Abstract</x> Purpose To evaluate wall shear stress (WSS) estimations in an in vitro and in vivo intracranial aneurysm, WSS was estimated from phase contrast magnetic resonance imaging (PC‐MRI) and compared with computational fluid dynamics (CFD). Materials and Methods First, WSS was estimated using a high‐resolution in vitro PC‐MRI measurement under steady and pulsatile flow conditions and compared with CFD simulations. Second, WSS was estimated in steady PC‐MRI data acquired at different spatial resolutions. Third, WSS estimations in pulsatile in vivo data were compared with CFD. The direction and magnitude of WSS vectors were computed and compared. Results Quantitative agreement between PC‐MRI and CFD‐based WSS estimations was moderate for the phantom (Spearman ρ = 0.69). The WSS magnitude derived from PC‐MRI data was lower than CFD for both the in vitro and in vivo case. However, there was qualitative agreement between PC‐MRI and CFD, i.e. WSS vector direction was similar for both modalities. Circular WSS patterns were found both in vitro and in vivo for PC‐MRI and CFD. Increasing PC‐MRI resolution increased mean WSS magnitude and uncovered complex WSS patterns. Conclusion WSS patterns can be estimated based on PC‐MRI data in in vitro and in vivo aneurysm geometries. Similar WSS directions as CFD can be discerned. J. Magn. Reson. Imaging 2013;38:876–884. © 2013 Wiley Periodicals, Inc.